Nutritional habits of combat athletes - D. B. Nikityuk; A. V. Pogozheva; A. K. Baturin (National Electronic Information Consortium (NEICON), 2020)
The review presents modern data characterizing the features of the energy exchange of athletes engaged in combat sport. The general principles of diet formation for combat athletes taking into account the basis of optimal nutrition, dependence on the period of sports activity (training, competition, and recovery), the duration and intensity of physical exertion are described. Based on results of recent studies published by Russian and foreign authors, the substantiation for the energy density of chemical composition of the diet (the content of proteins, fats, carbohydrates, vitamins, macro- and microelement) and hydration regime of combat athletes is given. The issues of food distribution during the day are affected, depending on the training and competitive process. Particular attention is paid to the use of specialized products and dietary supplements, as well as personalization of nutrition, which is based on individual studying of the nutritional status of combat athletes.